Challenges of Community Empowerment in the Era of Industry Society 5.O - Suryadi Suryadi; Dessy Kushardiyanti; Reza Gusmanti (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2021)
The presence of society 5.0 as a technology-based human-centred concept of society requires humans to have a paradigm of a more critical, creative way of thinking, and balance between development and the ability to solve problems to improve the quality of life in a sustainable manner. The industrial sector must innovate to be able to provide recommendations on every consumer problem. The digital content industry is one of the industrial sectors that is considered to have a significant role, both in improving the economy and in building sustainability for the community. This study uses a conceptual review to review the concept of the digital content industry in the perspective of Society 5.0. There are two aspects examined in this research, namely the presence of social media and its role as a stage for mainstream media in supporting community activities in era 5.0 and the readiness of human resources (HR) in the adaptation process and welcoming sustainable development. Youtube and Tiktok have become social media platforms as a form of technology application container as a savior of human life that depends on and coexists with technology.